2019
DOI: 10.31486/toj.18.0081
|View full text |Cite
|
Sign up to set email alerts
|

Autograft vs Allograft Comparison in Pediatric Medial Patellofemoral Ligament Reconstruction

Abstract: Background: Patella instability and medial patellofemoral ligament (MPFL) injury are frequently encountered in pediatric patients. MPFL reconstruction is often chosen to treat this condition with good results; however, no consensus has been reached about which graft or technique to use. The purpose of this study was to evaluate the differences in graft survivorship, clinical outcomes (assessed with Kujala scores), and cost between autograft and allograft usage in MPFL reconstruction in pediatric patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Seven studies 4 , 7 , 8 , 14 , 16 , 23 , 24 met all criteria and were included in this systematic review ( Figure 1 ). The studies included 150 patients who underwent MPFLR with autograft and 193 with allograft ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies 4 , 7 , 8 , 14 , 16 , 23 , 24 met all criteria and were included in this systematic review ( Figure 1 ). The studies included 150 patients who underwent MPFLR with autograft and 193 with allograft ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Scores ranging from 85 to 100 are excellent, 70 to 84 are good, 55 to 69 are fair, and <55 are poor. Risk of bias for the 6 nonrandomized 4 , 7 , 8 , 14 , 23 , 24 studies was assessed according to the Risk Of Bias In Non-randomized Studies–of Interventions (ROBINS-I 25 ) tool, which incorporates an assessment of bias due to confounding, selection of participants, deviations from intended interventions, completeness of outcome data, selection of outcomes reported, and other sources of bias. For the remaining randomized study, 16 risk of bias was assessed according to the Cochrane Collaboration risk-of-bias tool (Version 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakening the already weaker medial structures by harvesting an adductor graft to use for reconstruction is not consistent with balancing the forces acting on the patellofemoral joint. Furthermore, in a recent retrospective review of gracilis autograft versus allograft in 56 pediatric patients from 2012 to 2015, Hendawi et al concluded that autograft had longer operating times and higher graft failure at an average of 13.8 months when compared with allograft [55]. Larger systematic reviews have shown comparable revision rates and postoperative functional outcome scores between autograft and allograft MPFL reconstruction in adult patients [15].…”
Section: Soft Tissue Correction: Mpfl Repair and Reconstructionmentioning
confidence: 99%
“…Different techniques have been described that seek to reconstruct the ligament, which vary according to the graft choice, form and method of fixation, tension, and anatomic insertion site. [5][6][7][8] The latter is the point of most controversy, describing multiple locations at the level of the patella and the femur.…”
mentioning
confidence: 99%